OPTIMALISASI KINERJA PEGAWAI PENGAWAS KETENAGAKERJAAN PASCA TERBENTUKNYA UNIT PELAKSANA TEKNIS DAERAH (UPTD) BALAI PENGAWASAN DI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI UTARA - Roberti Augustinus Kairupan; Johny R.E. Tampi; Deysi ., Tampongangoy (Sam Ratulangi University, 2021)
The purpose of this research is to know directly the optimization of the performance of labor inspectors after the formation of the UPTD Balai Pengawas at the Department of Manpower and Transmigration of North Sulawesi Province. The research design used in this study used a descriptive method with a qualitative approach. The research focus is based on aspects of work quality, quantity of work, use of time and employee cooperation. There were 10 informants who were taken using purposive sampling technique with data collection techniques using interviews, observation and documentation which were analyzed by reducing data, displaying data and verification. The results showed that the optimization of employee performance is the focus of all government agencies and organizations in carrying out their duties. Satisfactory performance will be an asset and selling power of agencies and organizations where employees are valuable human resources who can help achieve goals. The conclusions of the research results indicate that the performance of supervisory employees in the Manpower and Transmigration Office of North Sulawesi Province needs to be optimized, where the performance needs to be directly supervised by the head of the supervisory office himself. It aims to improve performance so that the results achieved are as desired as a form of achievement as expected effectively and efficiently.